Minimal residual disease-guided treatment deintensilication for children with Acute Lyrnphoblastic Leukemia: results from the Malaysia-Singapore Acuten Lymphobiastic Leukemia 2003 Study - Yeoh, A.E.J.; Ariffin, H.; Chai, E.L.L.; Kwok, C.S.N.; Chan, Y.H.; Ponnudurai, K.; Campana, D.; Tan, P.L.; Chan, M.Y.; Kham, S.K.Y.; Chong, L.A.; Tan, A.M.; et al. (American Society of Clinical Oncology, 2012)
Purpose To improve treatment outcome for childhood acute lymphoblactic leukemia (ALL, we designed the Malaysia-Singapore ALL 2003 study with treatment stratification based on presenting clinical and genetic features and minimal residual disease (MRD) levels measured by polymerase chain reaction targeting a single antigen-receptor gene rearrangement. Patients and Methods Five hundred fifty-six patients received risk-adapted therapy with a modified Berlin-Frankfurt-Munster-All treatment. High-risk ALL was defined by MRD ≥ 1 x 10¯³ at week 12 and/or poor prednisolone response, BCR-ABL1, MLL gene rearrangements, hypodiploid less than 45 chromosomes, or induction failure; standard-risk ALL was defined by MRD ≤ 1 x 10¯4 at weeks 5 and 12 and no extramedullary involvement or high-risk features. Intermediate-risk ALL included all remaining patients. Results Patents who lacked high-risk presenting features (85.7%) received remission induction therapy with dexamethasone, vincristine, and asparaginase, without anthracyclines. Six year event-free survival (EFS) was 80.6% ± 3.5%; overall survival was 88.4% ± 3.1%. Standard-risk patients (n=172;31%) received significantly deintensified subsequent therapy without compromising EFS (93.2% ± 4.1%). High-risk patients (n=101;18%) had the worst EFS (51.8% ± 10%); EFS was 83.6% ± 4.9% in intermediate-risk patients (n=283;51%) Conclusion Our results demonstrate significant progress over previous trials in the region. Three-drug remission-induction therapy combined with MRD-based risk stratification to identify poor responders is an effective strategy for chilhood ALL.